Konflik Interpersonal di Lingkungan Kampus: Analisis Strategi dan Taktik Konflik dalam Kasus Kekerasan Mahasiswi UIN Sultan Syarif Kasim - Tira Felia Ramadhani; Asti Listiana; Rahmat Dion Gigani; Khoirunnisa Alim Fadhila; Sherafina Zahra Nayla Armand; Saliman Saliman; Yumi Hartati (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study is motivated by the increasing occurrence of interpersonal conflicts in higher education institutions that have the potential to escalate into violence if not managed effectively. One notable case is the stabbing of a female student at UIN Sultan Syarif Kasim Riau, which illustrates the escalation of conflict resulting from the failure of peaceful conflict resolution. This study aims to analyze the conflict escalation process and identify the strategies and tactics employed by the parties involved. The research adopted a qualitative approach using a case study design. Data were collected through document analysis by utilizing secondary sources, including news reports, scholarly articles, and relevant literature. The research subjects consisted of the perpetrator and the victim involved in the conflict. The findings indicate that the conflict originated from unresolved personal issues and intensified due to uncontrolled emotions, miscommunication, and the absence of open conflict resolution. The perpetrator employed a competing strategy characterized by aggressive and confrontational tactics, whereas the victim tended to adopt an avoiding strategy by withdrawing from the conflict. The lack of effective communication and mediation mechanisms caused the conflict to become destructive and ultimately resulted in violent behavior. This study highlights the importance of effective conflict management, open communication, and the active role of educational institutions in preventing interpersonal conflicts from escalating into acts of violence.